Dynamical Analysis of a Nitrogen-Phosphorus-Phytoplankton Model - Yunli Deng; Min Zhao; Hengguo Yu; Yi Wang (Discrete Dynamics in Nature and Society)
This paper presents a nitrogen-phosphorus-phytoplankton model in a water ecosystem. The main aim of this research is to analyze the global system dynamics and to study the existence and stability of equilibria. It is shown that the phytoplankton-eradication equilibrium is globally asymptotically stable if the input nitrogen concentration is less than a certain threshold. However, the coexistence equilibrium is globally asymptotically stable as long as it exists. The system is uniformly persistent within threshold values of certain key parameters. Finally, to verify the results, numerical simulations are provided.